Enhancing software development cost control by forecasting the cost of rework: preliminary study - Tarig Ahmed Khalid; Eng-Thiam Yeoh (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Industrial reports show massive cost overruns associated with software projects. The cost of software reworks constitutes a large portion of the overall cost, reflecting a substantial challenge in cost control. Earned value management (EVM) is the most recognized model for project cost control. However, it shows many limitations in forecasting the software project cost, leading to a considerable challenge in cost control. Nevertheless, the major EVM limitation found is its inability to forecast the cost of software rework. This research investigated the factors affecting this limitation and suggests an enhanced EVM model. The significant contribution of this research is its incorporation of software-related factors into the EVM model. We introduced the software rework index (SRI), which is incorporated into the traditional EVM model to enhance its predictability of the software project cost at completion, including the rework cost. We defined the SRI in terms of two factors: product functional complexity and the team competency. Finally, we evaluated the proposed model using a dataset drawn from five actual projects. The results showed a significant enhancement in forecasting accuracy.